2021
DOI: 10.1017/dce.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Universal Digital Twin - A Dynamic Knowledge Graph

Abstract: This paper introduces a dynamic knowledge-graph approach for digital twins and illustrates how this approach is by design naturally suited to realizing the vision of a Universal Digital Twin. The dynamic knowledge graph is implemented using technologies from the Semantic Web. It is composed of concepts and instances that are defined using ontologies, and of computational agents that operate on both the concepts and instances to update the dynamic knowledge graph. By construction, it is distributed, supports cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…The design of the World Avatar has been demonstrated as one way to implement a comprehensive Universal Digital Twin, for example a digital twin of the UK (Akroyd et al, 2021). The design confers a number of advantages which include the adoption of a distributed architecture that supports a uniform interface to query multiple data sources, the ability to use logical reasoning to verify the consistency of semantic models (Devanand et al, 2021), and a mechanism that allows computational agents to interact to answer questions (Zhou et al, 2019(Zhou et al, , 2020.…”
Section: A Universal Digital Twinmentioning
confidence: 99%
See 4 more Smart Citations
“…The design of the World Avatar has been demonstrated as one way to implement a comprehensive Universal Digital Twin, for example a digital twin of the UK (Akroyd et al, 2021). The design confers a number of advantages which include the adoption of a distributed architecture that supports a uniform interface to query multiple data sources, the ability to use logical reasoning to verify the consistency of semantic models (Devanand et al, 2021), and a mechanism that allows computational agents to interact to answer questions (Zhou et al, 2019(Zhou et al, , 2020.…”
Section: A Universal Digital Twinmentioning
confidence: 99%
“…This is a complex challenge and the ability to explore and assess different options can be aided through digitalization (Inderwildi et al, 2020). Dynamic knowledge graph technology developed as part of the World Avatar project (Eibeck et al, 2019; The World Avatar, 2021a) has been shown to provide an architecture that is suitable for implementing a Universal Digital Twin that can support the analysis of choices involving complex systems that is inherent to this type of challenge (Akroyd et al, 2021; CMCL Innovations, 2021). In this approach, autonomous computational agents interact to perform tasks including updating the knowledge graph to ensure that it remains current in time, simulating the behavior of systems and sending responses back to the physical world.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations